Endoplasmic reticulum stress in human skeletal muscle: any contribution to sarcopenia? - Deldicque, Louise (Frontiers in Physiology, 2013)
Skeletal muscle is vital to life as it provides the mechanical power for locomotion, posture and breathing. Beyond these vital functions, skeletal muscle also plays an essential role in the regulation of whole body metabolism, e.g. glucose homeostasis. Although progressive loss of muscle mass with age seems unavoidable, it is critical for older people to keep the highest mass as possible. It is clear that the origin of sarcopenia is multifactorial but, in the present review, it was deliberately chosen to evaluate the likely contribution of one specific cellular stress, namely the endoplasmic reticulum (ER) stress. It is proposed that ER stress can: 1) directly impact muscle mass as one fate of prolonged and unresolved ER stress is cell death and; 2) indirectly create a state of anabolic resistance by inhibiting the mammalian target of rapamycin complex 1 (mTORC1) pathway. With age, many of the key components of the unfolded protein response, such as the chaperones and enzymes, display reduced expression and activity resulting in a dysfunctional ER, accelerating the rate of proteins discarded via the ER-associated degradation. In addition, ER stress can block the mTORC1 pathway which is essential in the response to the anabolic stimulus of nutrients and contractile activity thereby participating to the well-known anabolic resistance state in skeletal muscle during ageing. As exercise increases the expression of several chaperones, it could anticipate or restore the loss of unfolded protein response components with age and thereby reduce the level of ER stress. This hypothesis has not been tested yet but it could be a new mechanism behind the beneficial effects of exercise in the elderly not only for the preservation of muscle mass but also for the regulation of whole body metabolism.